Biodegradation of Coir and Sisal Applied in the Automotive Industry - Salazar, V. L. P.; Leão, Alcides Lopes [UNESP]; Rosa, D. S.; Gomez, J. G. C.; Alli, R. C. P. (Springer/plenum Publishers, 2011)
This paper discusses the results of biodegradability tests of natural fibers used by the automotive industry, namely: coir, coir with latex, and sisal. The biodegradation of coir, coir with latex, and of sisal fibers was determined by monitoring the production of carbon dioxide (CO(2)) (IBAMA-E.1.1.2, 1988) and fungal growth (DIN 53739, 1984). The contents of total extractives, lignin, holocellulose, ashes, carbon, nitrogen and hydrogen of the fibers under study were determined in order to ascertain their actual content and to understand the results of the biodegradation tests. The production of CO(2) indicated low biodegradation, i.e., about 10% in mass, for all the materials after 45 days of testing; in other words, no material inhibited glucose degradation. However, the percentage of sisal fiber degradation was fourfold higher than that of coir with latex in the same period of aging. The fungal growth test showed a higher growth rate on sisal fibers, followed by coir without latex. In the case of coir with latex, we believe the fungal growth was not intense, because natural latex produces a bactericide or fungicide for its preservation during bleeding [1]. An evaluation of the materials after 90 days of aging tests revealed breaking of the fibers, particularly sisal and coir without latex, indicating fungal attack and biodegradation processes.
Keywords: Biodegradation; Coir; Sisal; Composites; Lignocellulosic fibers